(3GdebGdGJ aj GdMSGHs - (3CHh GdYHGS CMeO Hf eMeO Hf YKeGf GdCROj GdYOhj GdeQGcTj GHf GdHfGA, GHf GdHfGA,J (B721 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGdhMOGfjI hGdbOe GdPi CNQL GdCTjGA Edi GdhLhO ef GdYOe s
(3BNQgG (B:s
(3ced LejY cJGH GdebGdGJ dGHf GdHfGA ai GdMSGH s
(3Vef eLehY , JQJjHgG (B: 3s
(3GdfSNI HgG MhGTs
(3cJHJ CQbGe GdebGdGJ hGdGHhGH hGdCYOGO HGdMeQIs
(3fSNI fajSIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdQjGVjGJs